Reviving The Legacy: The Role of Islamic Education in Patani, South Thailand - Fatonah Salaeh (SYAMIL: Journal of Islamic Education, 2023)
Patani is a region located in the southern part of Thailand, bordering Malaysia. It has a rich and diverse cultural heritage that is deeply rooted in Islam. For centuries, the people of Patani have maintained a unique identity that reflects their Islamic faith, traditions, and way of life. One of the key pillars of this identity is the education system, which plays a vital role in preserving and transmitting the values and teachings of Islam to the younger generation. The purpose of this research is to explore the current state of Islamic education in Patani, its challenges, and its role in preserving the cultural and spiritual heritage of the region. The study aims to provide insights into the efforts being made to revive the legacy of Islamic education in Patani and the impact of these efforts on the community. This research utilizes a qualitative research method, specifically, a case study approach. Data were collected through interviews with key stakeholders in the region, including religious scholars, educators, and community leaders. Secondary sources, such as academic articles and reports, were also consulted to provide a broader context for the study. The findings of this research suggest that the traditional Islamic education system in Patani is facing numerous challenges, including the impact of modernization and globalization, the ongoing conflicts in the region, and the limited access to resources and funding. However, there are also promising developments, such as the establishment of new Islamic schools that incorporate modern subjects into their curriculum and the use of technology to enhance the learning experience. The study also highlights the important role of Islamic education in promoting peace, harmony, and understanding in the region. Overall, this research contributes to a deeper understanding of the importance of Islamic education in Patani and the challenges and opportunities facing the system. The study provides insights into the efforts being made to revive the legacy of Islamic education in the region and their potential impact on the community.